(untitled) (Journal of Educational Sciences, 2016)
In the conditions of entry of Kazakhstan into world educational space need of carrying out comparative researches of educational systems is staticized. Also it is a tendency in the conditions of the being globalized world community it is traced in many countries, regions. Modern development of comparative pedagogics as sciences is characterized by intensive enrichment of methodology and a technique of carrying out researches: are used ethno cultural, interdisciplinary, paradigmal, resource approaches. And also methods of modeling, technologization, content analysis. Within this article it would be desirable to answer questions of features of use of the content analysis in comparative and pedagogical research: carrying out structure, types of selections, analysis units, etc. During an era of the globalization and integration processes happening in the worlds education for effective carrying out comparative and pedagogical researches new tools, methods, technologies which need to be introduced already when training teachers are necessary. Apparently from this work the content analysis is an irreplaceable method of research of educational systems and has big prospects of development.